Autism Spectrum Disorder and Oral Healthcare: A Qualitative Study of Parents’ Perspectives in Padang City, Indonesia - Ningrum, Valendriyani; Bakar, Abu (Odonto : Dental Journal, 2023)
Background: Children with autism spectrum disorder, particularly those with mental and behavioral impairments, are affected regarding their oral health and impact their quality of life. Furthermore, perceptions of parents are also important in assessing the planning appropriate oral healthcare. The purpose of this study was to explore parent’s perspectives regarding barriers oral healthcare, tooth brushing behavior and the recommendation strategies to improve oral health status among individual with ASD in Padang city, Indonesia.Method: A purposive sample of six parents in public autism care centre in Padang city participated in focus groups addressing barriers maintain oral healthcare. Focus groups were transcribed and coded using qualitative content analysis. Primary themes included barriers oral healthcare, toothbrushing behavior and recommendations to improve oral healthcare. Content analysis was performed using NVivo software.Result: Parents noted barriers conducted oral hygiene such as drooling, tongue thrust and hard to focus relatively. Mothers noted general improvements in awareness of control diet and have used several media to help their children understand how to brush their teeth properly. Knowledge gaps included until when parents should help children brush their teeth and special oral healthcare. They expect that in the future, the government more attention to oral health of individuals with special needs. The role of the general dentist is crucial, and they expect the dentist to be more patient when caring with patients with special needs.Conclusion: Our findings indicate a need for comprehensive educational intervention and improved communication from policy maker, dentist, public health and prevention leaders in oral health care and dental hygienists to increase oral healthcare knowledge and practice of parents with ASD to better quality of life